Technique to study blood cells in Trachemys venusta venusta, Staurotypus triporcatus and Rhinoclemmys areolata - Hernández-Guzmán, Javier; Peraza-Gómez, Viridiana; Pérez-De la Cruz, Manuel; Torres-De la Cruz, Magdiel; Uscanga-Martínez, Arkady; Arias-Rodriguez, Lenin (Ecosistemas y Recursos Agropecuarios, 2025)
Turtles are organisms with high vulnerability due to the impact on their ecosystems and the lack of biological knowledge. Hematological studies in chelonians are limited by the absence of specific techniques-procedures; for this reason, adopted methodologies are not always appropriate. The study aim was to compare variations in fixatives concentrations, Giemsa staining versus exposure times on blood smears from Trachemys venusta venusta, Staurotypus triporcatus and Rhinoclemmys areolata. The comparison of pure methanol (99.8%) against denatured ethanol (70%) was carried out with exposure of 0.5, 1.0, 5.0 and 10 min. In the staining tests with Giemsa (10%), the exposure of 1, 5, 10 and 20 min was used and with the Giemsa stock solution the staining of 5, 10, 20 and 30 seconds was tested too. The results shown that increasing the exposure time in methanol, significantly increases the number of cells with damage to the membrane and cellular structure. In the samples with ethanol, low records of atrophy were observed. When 10% Giemsa was used together with the staining increase, a significant decrease in erythrocytes without membrane damage was observed. The employment of Giemsa stock solution rises the cells without damage. The best fixative was the denatured ethanol and staining with 10 seconds in Giemsa stock solution. With the suggested method, it will be possible to obtain high-quality blood cells for studies in basic and applied science as well as in clinical practices.
Keywords: erythrocytes; ethanol; hematology; methanol; freshwater turtles